Translation : A visual trip operated and articulated by M/M (Paris) with the Dakis Joannou collection. - Bourriaud, Nicolas; Sanchez, Marc; Sans, Jérôme (Athene : Deste Foundation for Contemporary Art, 2006)
Beecroft, Vanessa ; Bevilacqua, Michael ; Bickerton, Ashley ; Cai Guo-Qiang ; Cattelan, Maurizio ; Dawson, Verne ; Greene, Matt ; Kelley, Mike ; Koons, Jeff ; Lou, Liza ; Napurrula, Ningura ; Neshat, Shirin ; Murakami, Takashi ; Noland, Cady ; Ofili, Chris ; Orozco, Gabriel ; Shonibare, Yinka ; Sikander, Shahzia ; Kosuth, Joseph ; Walker, Kara ; Ward, Nari ; Wool, Christopher
Translation. Palais de Tokyo Paris. 2005-06-23. 2005-09-18
boek